The Optimal level of variation of Nike and Adidas Sporting Brands in Mashhad Sporting Stores - Dadrasmoghada, Amir; Ali Sahebkaran, Mohammad; Khosrou Etezad, Seyed; KHoshbakhti, Jafar; Barbaar, Ali (International Journal of Psychosocial Rehabilitation, 2021)
The product variation of every sporting brand plays an important role in the final choice of customers. This issue is important because the optimal level of variation of sporting brands can lead to decision-making in designing sporting product lines for managers. The data required for conducting this research collected from 140 sporting stores in Mashhad in 2019. In this research it has been tried to determine the optimal level of the variation of the sporting brands using the seemingly unrelated system of equation and optimization algorithm of particle swarm. The results of the optimization algorithm of the particle swarm showed that based on the optimal level of brand variation and the findings of this study, overall Nike brand should reduce 5, 2, and 10 types of their sporting shoes in large, medium and small stores, respectively. Adidas brand also should remove 11, 5, and 4 types of its sporting shoes in large, medium and small stores of Mashhad market, respectively. Also, the finding of this study suggests that the reduction of the level of Nile variation in large and medium stores should be less than Adidas brand, and the reduction of Adidas brand must be more in large stores, which is reversed for small stores.